TUWO: MODEL SUSTAINABILITY DIGITAL MARKETING SEBAGAI JALAN PINTAS UMKM BERSAING DI ERA SOCIETY 5.0 - Febrianur Ibnu Fitroh Sukono Putra; Amron Amron; Diana Aqmala; Awanis Linati Haziroh (Prosiding Seminar Nasional Akuntansi dan Manajemen (SENAMA), 2022)
Digital marketing is the answer to internationalization several obstacles of micro, small, and medium enterprises (MSMEs) in dealing with the society 5.0 era market dynamics. The virtual world has emerged as a promising platform for various marketing activities can significantly encourage MSMEs to improve business performance. The research aims to improve business performance by implementing a digital marketing sustainability model so it can be a solution for MSMEs to penetrate the international market in the society 5.0 era. The research method is an exploratory qualitative approach by collecting data based on in-depth interviews with related informants. The sampling technique is purposive sampling, in which the main criteria are MSMEs assisted by the Central Java Government. The research analysis flow is data collection, data reduction, data presentation, and concluding. The results show the "TUWO" solution model can be implemented in two ways, including (1) education and increasing digital marketing knowledge; (2) mentoring and business model development. This research implies a multiplier effect by improving MSME business performance at the international level through the government's role in facilitating online single submission programs to monitors in an integrated manner, so another government can adopt the successful implementation later of the "TUWO" model.